Multivariate MOF nanozyme utilizes glucose-activated self-cascade strategy for enhanced antibacterial efficacy and accelerated diabetic wounds healing - Yuxin Huang; Dixi Chen; T. M. Wong; Baolin Li; Yongxin Shi (APL Materials)
The impaired immune function observed in diabetic patients significantly increases their susceptibility of diabetic wounds to bacterial infections. Conventional treatment for bacterial infections relies heavily on antibiotics; however, this approach is often accompanied by the development of bacterial resistance. In this study, a nanozyme (Q@CuMn@G) exhibiting exceptional antibacterial efficacy with the capability to circumvent drug resistance was ingeniously designed. It operates through the generation of hydroxyl radicals (•OH) via a self-cascade reaction. The glucose oxidase (GOx) encapsulated within the Cu-metal–organic framework (MOF) generates H2O2 by degrading glucose present in the wound environment, which is subsequently catalyzed by the Cu-MOF to produce •OH, thereby exerting potent antibacterial effects. Meanwhile, MnO2 loaded within Cu-MOF generates O2, ameliorating the hypoxic environment of the wound and further supporting the degradation of glucose by GOx. Quaternized chitosan is employed as a shell to envelop the nanozyme, thus preventing the rapid degradation of GOx. In vitro experiments demonstrated that Q@CuMn@G exhibits sustained release of •OH and significant bactericidal effects against Escherichia coli and Staphylococcus aureus, confirming the high antibacterial activity of the nanozyme. Moreover, in vivo experiments revealed that Q@CuMn@G effectively kills bacteria in infected diabetic wounds, modulates the immune microenvironment, and accelerates wound healing, achieving a healing ratio of 96.78%. This study employs the Q@CuMn@G nanozyme to achieve highly effective antibacterial efficacy through chemodynamic therapy, thereby offering an innovative strategy for antibiotic-free treatment of diabetic wound repair.